(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
P2X receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on P2X Receptors [46, 134]) have a trimeric topology [118, 132, 177] with two putative TM domains, gating primarily Na+, K+ and Ca2+, exceptionally Cl-. The Nomenclature Subcommittee has recommended that for P2X receptors, structural criteria should be the initial criteria for nomenclature where possible. X-ray crystallography indicates that functional P2X receptors are trimeric and three agonist molecules are required to bind to a single receptor in order to activate it [132, 88, 96, 161]. Native receptors may occur as either homotrimers (e.g. P2X1 in smooth muscle) or heterotrimers (e.g. P2X2:P2X3 in the nodose ganglion [251], P2X1:P2X5 in mouse cortical astrocytes [146], and P2X2:P2X5 in mouse dorsal root ganglion, spinal cord and mid pons [50, 207]. P2X2, P2X4 and P2X7 receptors have been shown to form functional homopolymers which, in turn, activate pores permeable to low molecular weight solutes [229]. The hemi-channel pannexin-1 has been implicated in the pore formation induced by P2X7 [188], but not P2X2 [38], receptor activation.